Distribusi dan Kemelimpahan Meiofauna di Hulu Sungai Code Yogyakarta - Hariyati, Riche - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2007)
This research is aimed to study distribution and abundance of meiofauna and the quality of physicochemicalcharacteristics of uppersite of code river and up stream river code Yogyakarta province. Samples weretaken using modified Pysto style corer and were located based on habitat types specific river, which are pool, riffle,rapid, left side and right side of water column. Sample taken four times for each zone. The parameter of for waterquality measured were dissolved oxygen. Water current, alkalinity and pHResult from the analysis showed that the abundance of meiofauna at code river the highest at left side zone.Which was 537.806 individu/m3 with relative abundance was 28,09% result from physico chemical parameter ofdissolved oxygenbetween 5,44 ppm – 6,0 ppm, alkalinity 20 ppm – 25 ppm , pH 7,10 – 7,18.and watercurrenntmeasured between 0,03 m/sec – 0,49 m/sec. The abundance of meiofauna at code river was dominated bygroup of Nematodes horizontal distribution of the fauna was the widest for Nematodes ostracoda, Rhizopoda andinsecta. Physico chemicalquality of code river water was relative good for meiofauna habitat and other waterorganisms